2024
DOI: 10.1161/jaha.123.030560
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy History at 40 Years of Age as a Marker of Cardiovascular Risk

Liv G. Kvalvik,
Rolv Skjærven,
Gerhard Sulo
et al.

Abstract: Background Individual pregnancy complications are associated with increased maternal risk of cardiovascular disease. We assessed the link between a woman's total pregnancy history at 40 years of age and her relative risk of dying from atherosclerotic cardiovascular disease (ASCVD). Methods and Results This population‐based prospective study combined several Norwegian registries covering the period 1967 to 2020. We identified 854 442 women born after 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Therefore, the investigation by Kvalvik et al 5 in this issue of the Journal of the American Heart Association ( JAHA ) is an important contribution on the relationship of pregnancy history, APOs, and future cardiovascular events. The aim of this population‐based, prospective study was to determine the association between a woman's complete pregnancy history (defined as total number of pregnancies and number of complicated pregnancies at 40 years old) and risk of death from atherosclerotic CVD (ASCVD) between the ages of 40 and 69 years.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the investigation by Kvalvik et al 5 in this issue of the Journal of the American Heart Association ( JAHA ) is an important contribution on the relationship of pregnancy history, APOs, and future cardiovascular events. The aim of this population‐based, prospective study was to determine the association between a woman's complete pregnancy history (defined as total number of pregnancies and number of complicated pregnancies at 40 years old) and risk of death from atherosclerotic CVD (ASCVD) between the ages of 40 and 69 years.…”
mentioning
confidence: 99%
“…Kvalvik et al 5 demonstrated that, compared with women at the age of 40 years with 3 uncomplicated pregnancies (reference), an increased risk for ASCVD death was noted in nulliparous women (hazard ratio [HR], 2.9 [95% CI, 2.4–3.4]) and women with a single uncomplicated pregnancy (HR, 2.2 [95% CI, 1.9–2.7]). However, at each parity, the trajectory for risk of ASCVD death significantly increased with each number of complicated pregnancies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study by Kvalvik et al examined the number of pregnancies and the complications associations with each pregnancy among a Norwegian population‐based prospective study following women from 1967 to 2020. 9 They found that at 40 years of age, the risk of atherosclerotic cardiovascular disease death increased with the number of complicated pregnancies in a dose–response manner, and women with ≥4 pregnancy complications had a 23‐fold increase in adverse outcomes. The accompanying editorial by Johnson highlights the need for future research on effective strategies to mitigate the impact of pregnancy factors, especially in more racially and ethnically diverse populations.…”
mentioning
confidence: 99%